"Be creative and you will reach more people": youth's experiences participating in an arts-based social action group aimed at mental health stigma reduction. Issue 1 (2nd January 2020) - Kennedy, Heather; Marley, Maeve; Torres, Kristen; Edelblute, Anthony; Novins, Douglas
ABSTRACT: Background : Starting in 2013, the Mental Health Youth Action Board, made up of 15 teens ages 15–18, was created to advise a large children's hospital on improvements in mental health care and produce social action projects to impact community perceptions of mental health. Methods : This participatory qualitative case study explored the experiences of 14 young people who participated in the Mental Health Youth Action Board between 2013 and 2016. Results : There were two higher order themes: process and outcomes. Process-related themes included how this was a unique leadership experience, the importance of the arts-based approach, and value of the intentionally constructed storytelling process. These processes led to youth growing as advocates for mental health. Conclusions : Arts-based approaches to social action that allow youth to share personal experiences of stigmatized topics can promote healing and support their growth as leaders.